Phylogenomic analysis of the Porphyromonas gingivalis - Porphyromonas gulae duo: approaches to the origin of periodontitis - Morales-Olavarría, Mauricio; Nuñez-Belmar, Josefa; González, Dámariz; Vicencio, Emiliano; Rivas-Pardo, Jaime Andres; Cortez, Cristian; Cárdenas, Juan P. (Frontiers in Microbiology, 2023)
Porphyromonas gingivalis is an oral human pathogen associated with the onset and progression of periodontitis, a chronic immune-inflammatory disease characterized by the destruction of the teeth-supporting tissue. P. gingivalis belongs to the genus Porphyromonas, which is characterized by being composed of Gram-negative, asaccharolytic, non-spore-forming, nonmotile, obligatory anaerobic species, inhabiting niches such as the oral cavity, urogenital tract, gastrointestinal tract and infected wound from different mammals including humans. Among the Porphyromonas genus, P. gingivalis stands out for its specificity in colonizing the human oral cavity and its keystone pathogen role in periodontitis pathogenesis. To understand the evolutionary process behind P. gingivalis in the context of the Pophyoromonas genus, in this study, we performed a comparative genomics study with publicly available Porphyromonas genomes, focused on four main objectives: A) to confirm the phylogenetic position of P. gingivalis in the Porphyromonas genus by phylogenomic analysis; B) the definition and comparison of the pangenomes of P. gingivalis and its relative P. gulae; and C) the evaluation of the gene family gain/loss events during the divergence of P. gingivalis and P. gulae; D) the evaluation of the evolutionary pressure (represented by the calculation of Tajima-D values and dN/dS ratios) comparing gene families of P. gingivalis and P. gulae.Our analysis found 84 high-quality assemblies representing P. gingivalis and 14 P. gulae strains (from a total of 233 Porphyromonas genomes). Phylogenomic analysis confirmed that P. gingivalis and P. gulae are highly related lineages, close to P. loveana. Both organisms harbored open pangenomes, with a strong core-to-accessory ratio for housekeeping genes and a negative ratio for unknown function genes. Our analyses also characterized the gene set differentiating P. gulae from P. gingivalis, mainly associated with unknown functions. Relevant virulence factors, such as the FimA, Mfa1, and the hemagglutinins, are conserved in P. gulae, P, gingivalis, and P. loveana, suggesting that the origin of those factors occurred previous to the P. gulae-P.gingivalis divergence. These results suggest an unexpected evolutionary relationship between the P. gulae-P. gingivalis duo and P. loveana, showing more clues about the origin of the role of those organisms in periodontitis.